Jailer of freedom and enemy of growth?* The role of personal and social identities in educational choices. Issue 5 (2nd September 2016) - Autiero, Giuseppina; O'Higgins, Niall
Abstract: This paper develops a theoretical and empirical model on the influence of identity on educational choices which extends the existing literature in several directions. The theoretical model proposed here allows schooling choices to be independently influenced by both personal and social identities and, in contrast to previous work, the proposed empirical counterpart is derived directly from the theoretical model. The use of UK's British Cohort Study on individuals born in 1970 allows us to identify with precision the relevant explanatory factors and to appropriately control for potentially confounding factors. Both social and personal identities are found to have substantial and statistically significant effects on educational participation decisions and these impacts are robust to a variety of specifications. The key implication is that socio-psychological factors play an important role in children's school performance through their direct influence on the utility derived from studying.